Pendidikan Jiwa Perspektif Hamka dalam Tasawuf Modern - Nufus, Dewi Hayati (Tawazun: Jurnal Pendidikan Islam, 2021)
Education is an essential need for humans that need a method so that it can be implemented in order to achieve educational goals that have relevance to human existence on earth. Islamic education is the instilling and inculcation of adab and fundamental values that have to be prepared by all components of education related to moral, aesthetic, and spiritual values which are arranged in the philosophy of Islamic science. According to Hamka, education is particularly oriented to the values of human and nation existences. Hamka’s thoughts about education is a process to emerge namely the steadfast resolution of soul and it’s consistency. Therefore, the origin education is the education that revelead a numeruos knowledge and sciences that are more profound and can provide treasure and pleasure (bashirah) of the human heart and soul. The knowledge itself has to leverage on the goodness of human personality to his intelligence. Hamka education approaches which adequate to transform a man through his spiritual values by education of soul. This study uses a qualitative library research method with a modern Sufism approach from Hamka’s perspective. The purpose of this study is to analyze modern Sufism as an approach used in education of soul. The achievement of happiness is the actual goal of education which is expected to be able to emphasize that the actual orientation of happiness is not about materialistic and humanistic values. The precious happiness of human life is marifatullah or to recognize and to acknowledge of Allah Ta’ala The only God, and man with his existence on earth, as known as the caliph fiil ardh who has a calm soul, and steadfast in carrying out the responsibility and commitment in the world and hereafter. Abstrak Pendidikan adalah kebutuhan esensial bagi manusia yang memerlukan suatu metode agar dapat diaplikasikan dalam rangka mencapai tujuan pendidikan yang memiliki relevansinya dengan keberadaan manusia di muka bumi. Pendidikan Islam yang meliputi unsur penanaman nilai-nilai adab atau fundamental kehidupan harus mampu mempersiapkan seluruh komponen pendidikan yang berkaitan dengan nilai moral, estetis, spiritual yang tersusun dalam falsafah ilmu Islami. Pendidikan menurut Hamka yang berorientasi secara khusus pada nilai-nilai eksistensi manusia dan bangsa, yakni keteguhan jiwa, keistiqamahan/konsistensi adalah pendidikan yang dapat membuka ilmu-ilmu lain yang lebih mendalam dan dapat memberikan nikmat dan kesenangan (bashirah) hati dan jiwa manusia yang mempengaruhi kebaikan kepribadiannya hingga kecerdasannya. Oleh karenanya Hamka sangat mengedepankan pendidikan yang mampu merubah seseorang melalui nilai-nilai spiritualnya dengan pendidikan jiwa. Penulisan menggunakan metode kualitatif library research dengan pendekatan tasawuf modern perspektif Hamka. Tujuan penulisan adalah menganalisis tasawuf modern Hamka sebagai pendekatan yang digunakan dalam pendidikan jiwa. Capaian kebahagiaan yang merupakan tujuan pendidikan yang sebenarnya diharapkan mampu menegaskan kembali bahwa orientasi kebahagiaan adalah bukan pada nilai materialistik dan humanistik, namun nilai-nilai pemahaman manusia atas Tuhannya atau marifatullah, dan eksistensi dirinya di muka bumi, yakni sebagai khalifah fiil ardh yang memiliki jiwa yang tenang, dan teguh demi mengemban amanah kebahagiaan dunia dan orientasi kebahagiaan akhirat.